Physiological roles of regulated Ire1 dependent decay - Coelho, Dina S.; Domingos, Pedro M. (Frontiers in Genetics, 2014)
Ire1 is an important transducer of the Unfolded Protein Response (UPR) that is activated by the accumulation of misfolded proteins in the Endoplamic Reticulum (ER stress). Activated Ire1 mediates the splicing of an intron from the mRNA of Xbp1, causing a frame-shift during translation and introducing a new carboxyl domain in the Xbp1 protein, which only then becomes a fully functional transcription factor. Studies using cell culture systems demonstrated that Ire1 also promotes the degradation of mRNAs encoding mostly ER-targeted proteins, to reduce the load of incoming ER “client” proteins during ER stress. This process was called RIDD (regulated Ire1-dependent decay), but its physiological significance remained poorly characterized beyond cell culture systems. Here we review several recent studies that have highlighted the physiological roles of RIDD in specific biological paradigms, such as photoreceptor differentiation in Drosophila or mammalian liver and endocrine pancreas function. These studies demonstrate the importance of RIDD in tissues undergoing intense secretory function and highlight the physiologic role of RIDD during UPR activation in cells and organisms.